2009
DOI: 10.1098/rspb.2009.0584
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variability in species composition explained as seasonally entrained chaos

Abstract: The species composition of plankton, insect and annual plant communities may vary markedly from year to year. Such interannual variability is usually thought to be driven by year-to-year variation in weather conditions. Here we examine an alternative explanation. We studied the effects of regular seasonal forcing on a multi-species predator-prey model consisting of phytoplankton and zooplankton species. The model predicts that interannual variability in species composition can easily arise without interannual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(98 citation statements)
references
References 73 publications
5
92
1
Order By: Relevance
“…For the phenomenon we observed in western Gulf of Maine, we can focus on how change in bloom timing may affect the size and quality of phytoplankton in the context of zooplankton feeding and trophic transfer, while at the same time providing little inter-annual contrast in chlorophyll concentration. Bloom start date would likely result in different species assemblages that constitute the spring bloom each year (Dakos et al, 2009;Irigoien et al, 2000). The timing may also influence the size spectra and species composition of the bloom due to the effects of thermal conditions when the bloom develops (Barnes et al, 2011;Mousing et al, 2014) or due to the light regime affecting early versus late blooms (Polimene et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For the phenomenon we observed in western Gulf of Maine, we can focus on how change in bloom timing may affect the size and quality of phytoplankton in the context of zooplankton feeding and trophic transfer, while at the same time providing little inter-annual contrast in chlorophyll concentration. Bloom start date would likely result in different species assemblages that constitute the spring bloom each year (Dakos et al, 2009;Irigoien et al, 2000). The timing may also influence the size spectra and species composition of the bloom due to the effects of thermal conditions when the bloom develops (Barnes et al, 2011;Mousing et al, 2014) or due to the light regime affecting early versus late blooms (Polimene et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Phytoplankton fluctuations are therefore likely to affect food web dynamics. Although effects of seasonality on aquatic food webs have been investigated by various studies (e.g., Dakos et al, 2009;Koeller et al, 2009;McMeans et al, 2015), effects of environmental variability at shorter time scales on food web dynamics have received less attention. Experimental studies have shown that fluctuations in zooplankton abundances are strongly coupled to phytoplankton fluctuations, and may show predator-prey oscillations with typical periodicities of a few weeks (Fussmann et al, 2000;Benincà et al, 2009).…”
Section: Implications For Food Web Dynamicsmentioning
confidence: 99%
“…High interannual variability of the 12-month cycle is reflected in the low observed wavelet variance detected in many Chl-a series ( figure 5). This variability arises from many interactive processes of bloom dynamics, including external forcing (meteorological conditions, resource availability) and internal multispecies interactions (Dakos et al 2009;Platt et al 2010). -Six-month periodicity.…”
Section: Annual Cycles Of Phytoplankton Biomassmentioning
confidence: 99%
“…In addition, phytoplankton boom -bust cycles are not always a response of the entire community but often a reflection of population succession of individual taxa. Speciesspecific variation in resource requirement and trophic interactions can generate complex dynamical behaviours and trigger episodic bloom events (Dakos et al 2009). Consequently, fast biomass turnover of this physiologically and morphologically diverse group suggests that blooms can occur with varying intensity and at different times each year.…”
Section: Annual Cycles Of Phytoplankton Biomassmentioning
confidence: 99%